2010
DOI: 10.1128/aem.01914-09
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of the Volumetric “Bottle Effect” on Microbial Batch Growth

Abstract: We have analyzed the impact of surface-to-volume ratio on final bacterial concentrations after batch growth. We examined six bottle sizes (20 to 1,000 ml) using three independent enumeration methods to quantify growth. We found no evidence of a so-called volumetric bottle effect, thus contradicting numerous previous reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 19 publications
5
55
2
Order By: Relevance
“…These conditions could limit the strain growth. In general terms, it is referred to as the "bottle effect", which is the set of experimental variables that decrease vital functions and properties of growth in a body, when it is moved from its natural environment to an experimental one [36]. Our observations of microalgae biomass reduction under saline lab-conditions greater than 1 mol/L agree with the one reported by Cifuentes et al (1992) for D. salina Teodoresco from the subtropical South American hypersaline environments.…”
Section: Effect Of Salinitysupporting
confidence: 84%
See 1 more Smart Citation
“…These conditions could limit the strain growth. In general terms, it is referred to as the "bottle effect", which is the set of experimental variables that decrease vital functions and properties of growth in a body, when it is moved from its natural environment to an experimental one [36]. Our observations of microalgae biomass reduction under saline lab-conditions greater than 1 mol/L agree with the one reported by Cifuentes et al (1992) for D. salina Teodoresco from the subtropical South American hypersaline environments.…”
Section: Effect Of Salinitysupporting
confidence: 84%
“…This effect was much more acute in the case of cultures with N/P ratios below 5/1. Furthermore, in these cultures cell death could be occurring and therefore, a reduction of the microalgae biomass [36]. Otherwise, concerning N/P ratio of 14/1, some authors state that under these nonacute scarcity conditions, microalgae are capable of turning degrading pathways of nitrogen compounds, which would maintain a sufficient pool of intracellular nitrogen for its reproduction [37].…”
Section: Effect Of Nitrogen Limitation Nitrogen Deficiency and Air Bmentioning
confidence: 99%
“…This may be due to biofilm forming on the sides of the bottle, changes in substrate availability due to adsorption of cells, carbon or nutrients on glass surfaces, or unintended changes in turbulence patterns, chemistry, or trophic dynamics (Amy and Hiatt, 1989;Calvo-Díaz et al, 2011;Fogg and Calvario-Martinez, 1989). Bottle effects are likely enhanced in smaller volume, but I was not able to document dampened bottle effects when increasing the volume from 2.5L to 3.9L (Paper II, Paper III, Paper V) as previously documented (Hammes et al, (2010). This may not come as a surprise given that bottle effects are evident even in large scale (>1000 L) mesocosm incubations (Calvo-Díaz et al, 2011;Hosia et al, 2014;Rahav et al, 2016).…”
Section: Box 3 | the Bottle Effectmentioning
confidence: 55%
“…Past studies have suggested that a "bottle effect" may occur with natural water samples stored in plastic or glassware, where contact with such media can artificially increase microbial numbers in water samples and lead to experimental artefacts (Bischofberger et al 1990). On the other hand, Hammes et al (2010) found no evidence of significant bottle effects across a range of bottle sizes and surface area to volume ratios. Although we cannot discount the possibility that the artificial conditions used in this experiment may have elevated microbial abundance, and thereby enhanced DOC concentrations to some extent, a full experimental run using samples of only deionised water (without having rinsed out the bottles beforehand, so some microbes would still have been present) did not lead to increases in DOC, providing some evidence that our results were not due to an experimental artefact.…”
Section: Susceptibility Of Contrasting Waters To Photo-degradationmentioning
confidence: 66%